Identifikasi Penyebab Varian Material RM3100-0250P di PT. XYZ - Poerwanto, Cheryl; Adi, Prayonne (Jurnal Titra, 2019)
PT. XYZ is a manufacturing company engaged in filter industry in Indonesia, the study was conducted at PT. XYZ which focuses on the Production Department. The Production Departement has an important role in producing filters. The Production Department often experiences difference in inventory between the actual stock and the administrative counting system. The difference in inventory between the actual stock and the administrative counting system is called variant. This study will focus on variants that often occur in materials RM3100-0250P. The target that needs to be achieved is to avoid the occurrence of variants in the material RM3100-0250P. Repairs need to be done at PT. XYZ to avoid variants in the material RM3100-0250P.Improvement and processing of data that need to be used in this study is to use the help of applying six sigma with the DMAIC method. The DMAIC method will assist in research by conducting a search for the root of the problem and making improvements from the root of the problems that have been found. The tool that will be used to identity the root cause is to use the help of fishbone diagrams. Fishbone diagrams will help research to be able to correct any problems that arise up to the roots so that problems that occur become increasingly well controlled. The problem that needs to be improved is the material part and method. Material improvement that needs to be done is to determine the BOM standard material RM3100-0250P. The improvement that needs to be done on the method is to make the standard work steps appropriate for the problem reject in the administrative counting system.